Global macroeconomic developments and poverty - Díaz-Bonilla, Eugenio (International Food Policy Research Institute, 2008)
In the second half of the 1990s, a series of developments led to a renewed academic and policy interest in the intersection of macroeconomic policy and poverty issues in developing countries. The focus of that work was domestic macroeconomic policies. This paper, however, focuses on the international dimension and discusses the links between global macroeconomic conditions and poverty in developing countries since the 1960s. Of course, when analyzing policy impacts, both domestic and international aspects must be considered. However, debates about domestic policies, macro or otherwise, and their impacts on poverty cannot provide an accurate analysis of developing countries' alternatives and predicaments if they ignore the role, in many cases overwhelming, of external factors. That is the story this paper tries to tell. The objectives here are to present an overview of trends and cycles in the world economy, to summarize the events of the last half century in view of the current concerns about the likely economic slowdown in the United States and other industrialized economies, and to assess the possible repercussions on the rest of the world. The hope is that the paper will serve as background material for developing countries to better characterize potential scenarios and properly define policy options for the coming years, which look like they will be far less benign than the recent past.